Prison Violence, Gender, and Perceptions: Testing a Missing Link in Discretion Research - Bierie, David M. (American journal of criminal justice, 2012)
Criminal justice literature often suggests female social control agents (e.g., police, prison staff, and others) use force less often than male colleagues facing similar situations. Most explain this with reference to personal or social factors which are gendered, arguing role-pressures or differences in skill sets between men and women lead to different reactions by agents. However, part of the story may also be about assessment rather than reaction—men and women may diverge in how they recognize and interpret cues in some (particularly minor) violence situations. Testing this, survey data was drawn from a random sample of 2,077 staff working in all 112 Federal Prisons operating in 2005. By estimating fixed effects models (grouped on prison), as well as controlling for correlates of exposure within a given prison, male and female staff were compared with respect to their assessment of statistically similar violence events. The data showed that women assessed fewer minor assault events to have occurred than their male colleagues, yet the same number of serious violence events. This supports the argument that perceptions may play an important role in explaining gender differences in the use of discretion.